Changes in Ascorbic Acid, Total Polyphenol, Phenolic Acids and Antioxidant Activity in Juice Extracted from Coated Kiew Wan Tangerine During Storage at 4, 12 and 20°C - Tongchai Puttongsiri; Ratiporn Haruenkit (Agriculture and Natural Resources, 2010)
The aim of this research was to investigate changes in ascorbic acid, total polyphenol, phenolic acids and antioxidant activity in juice extracted from Kiew Wan tangerines (Citrus reticulate Blanco cv. Kiew Wan) coated with shellac. The coated fruits were stored for five weeks at 4, 12 and 20°C and samples were taken weekly for analysis. Ascorbic acid decreased during storage at all tested temperatures. The major phenolic acids found were ferulic acid followed by sinapic, caffeic and p-coumaric acid. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2 azinobis (3-ethylbenzothiazoline-6-sulfonate (ABTS) antioxidant activities increased during storage and were correlated with total polyphenol and phenolic acid contents. Sinapic, caffeic and p-coumaric acid levels were significantly correlated with the DPPH while ferulic acid was correlated with the ABTS. All phenolic acids increased during the early stage of storage at 4 and 12°C but decreased at the end. Weight loss of coated fruit during storage was in the range of 4–17%.